Relation of the Communist Regime Towards the Catholic Church in Croatia Between 1945 and 1952 - Josipović Batorek, Slađana (Poznańskie Studia Slawistyczne, 2016)
Based on historical facts, published and unpublished archival materials, this work provides concise analysis of relations between the Church and the state in Croatia between 1945 and 1952, that is from the period when the Communist Party of Yugoslavia became the ruling party until the break-up of diplomatic relations with the Holy See. Since this was a quite dynamic period in terms of socio-political changes, as well as Church-state relations, the article emphasizes only those aspects that constitute the foundation of the conflict between the Catholic Church and the communist regime such as religious education in schools and catholic clergy’s class associations. Moreover, in the introductory part of the work ideological and political causes of the conflict are briefly explained, as well as relations of the Church and the state in the post-war period with a view to better understanding of the position of the Catholic Church and the overall context of the catholic religious life in time to come.